Towards a non-empirical trailing edge noise prediction model. (23rd June 2016) - Stalnov, Oksana; Chaitanya, Paruchuri; Joseph, Phillip F.
Abstract: This paper extends previously published TNO-Blake model to predict airfoil broadband self-noise due to the interaction of a turbulent boundary layer with a sharp trailing edge. The main objectives of this paper are reduced the dependence on 'turning parameters'. The method presented herein combines an extension to Blake׳s model to predict the pressure fluctuation on the airfoil surface due to the turbulent boundary layer. Flat plate theory, with finite-chord effects included, is introduced to predict its subsequent radiation to the far field. The paper builds on recent advances in the prediction of the streamwise turbulent intensity profile to avoid the use of empirical relationships. Surface pressure spectra measurements are compared to predictions where agreement within 2 dB is obtained in the mid to high frequency range.